2008
DOI: 10.1021/ja0782504
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Structure of CH5+ by Dissociative Charge Exchange

Abstract: Dissociative charge exchange of CH5+ with Cs, coupled with quasiclassical trajectory calculations on an ab initio PES for CH5, has been used to probe the structure of the CH5+ cation. Product kinetic energy release distributions and branching ratios for CH5 --> CH4 + H and CH5 --> CH3 + H2 have been compared. The agreement of the product branching ratios provides evidence for the fluxional nature of CH5+.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
49
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 24 publications
(58 citation statements)
references
References 14 publications
(23 reference statements)
9
49
0
Order By: Relevance
“…Similar approaches were used previously describing other systems in which classical trajectories were initiated at geometries where electronic transitions to the ground electronic state occur. [22][23][24] This total energy corresponding to 4.46 eV relative to the OH͑r e ͒ +H 2 ͑r e ͒ asymptote, where "r e " denotes to the equilibrium bond length and is roughly the sum of the experimental energy 10 of 4.06 eV plus the sum of the OH and H 2 zero-point energies. ͓Hereafter all energies are given relative to OH͑r e ͒ +H 2 ͑r e ͒.͔ Trajectories were propagated on a new ground state adiabatic potential to determine the properties of the ground electronic state products.…”
Section: Introductionmentioning
confidence: 99%
“…Similar approaches were used previously describing other systems in which classical trajectories were initiated at geometries where electronic transitions to the ground electronic state occur. [22][23][24] This total energy corresponding to 4.46 eV relative to the OH͑r e ͒ +H 2 ͑r e ͒ asymptote, where "r e " denotes to the equilibrium bond length and is roughly the sum of the experimental energy 10 of 4.06 eV plus the sum of the OH and H 2 zero-point energies. ͓Hereafter all energies are given relative to OH͑r e ͒ +H 2 ͑r e ͒.͔ Trajectories were propagated on a new ground state adiabatic potential to determine the properties of the ground electronic state products.…”
Section: Introductionmentioning
confidence: 99%
“…However, most of these studies agreed in considering CH 5 + ion as a very fluxional species [63][64][65][66][67], whose basic components are a tripod CH 3 and a H 2 moiety. There are however some specific cases in which the coordination of carbon was found to be larger than four.…”
Section: Pentacovalent Carbon Atomsmentioning
confidence: 99%
“…This exceeds the bond energy of H2O, but it is very likely that a large fraction of the energy is carried by fast H-atoms, leaving the H2O in bound states that are highly vibrationally excited. Recent experimental work by Mann et al (2008) on the dissociation of H3O following charge exchange of H3O + with Caesium revealed that H2O is produced in excited sym-metric/asymmetric stretch modes coupled with low bending and rotational excitation. The fact that the majority of the H3O + ions undergoing dissociative recombination were initially in ground vibrational states with a rotational temperature of 20-60 K and that the majority of the available energy is partitioned to H2O internal energy would appear to have direct parallels with vibrational excitation of H2O molecules initially in low J, ground vibrational states in the collisionally-dominated region of the cometary inner coma.…”
Section: Refmentioning
confidence: 99%